2009
DOI: 10.1111/j.1468-1293.2009.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior pneumococcal vaccination on clinical outcomes in HIV‐infected adult patients hospitalized with invasive pneumococcal disease

Abstract: Background Recent studies in hospitalized patients with community‐acquired pneumonia have found a lower risk of bacteraemia and better clinical outcomes in patients who had previously received the 23‐valent pneumococcal polysaccharide vaccine (PPV) in comparison with unvaccinated individuals. The aim of this study was to assess the influence of prior PPV on clinical outcomes in HIV‐infected adult patients hospitalized with invasive pneumococcal disease (IPD). Methods This was an observational study of all cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
(55 reference statements)
0
7
0
1
Order By: Relevance
“…In this regard, some studies have found that pneumococcal polysaccharide vaccine is effective in preventing hospitalizations for pneumonia 8 and reduces the rates of ICU admission and inhospital mortality in immunosuppressed and nonimmunosuppressed patients with CAP or invasive pneumococcal disease. 15,2133 However, there is little evidence of vaccine protection for pneumonia. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies have found that pneumococcal polysaccharide vaccine is effective in preventing hospitalizations for pneumonia 8 and reduces the rates of ICU admission and inhospital mortality in immunosuppressed and nonimmunosuppressed patients with CAP or invasive pneumococcal disease. 15,2133 However, there is little evidence of vaccine protection for pneumonia. 30 …”
Section: Discussionmentioning
confidence: 99%
“…IgM+ memory B cells are depleted and pneumococcal-specific Ab responses to pneumococcal vaccination are impaired in HIV-infected patients, even in patients who have received long-term ART [25, 126]. Due to the high risk for HIV patients to develop IPD [25, 66, 68, 100, 127], research is critically important to better understand Ab concentrations against pneumococcal polysaccharide serotypes in PPV- and PCV-immunized HIV-infected individuals. Research studies have shown that PCV immunization initiated an enhanced serotypic-specific IgG response to PPV, which led to an increased Abs against PPS 14, 19F and 23F serotypes, both in HIV-infected individuals and healthy individuals, compared with those immunized with PPV alone, suggesting that immunization with both PPV and PCV induced a better protective effect [128-131].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have observed better clinical outcomes in patients who had previously received the PPV-23 compared with unvaccinated individuals [26,27]. We also observed this beneficial effect on the incidence of septic shock and survival in vaccinated patients with HIV infection who developed an invasive pneumococcal infection [28]. Regarding respiratory outcomes, FISMAN et al [27] found that prior receipt of pneumococcal vaccine was associated with a decreased risk of respiratory failure in a large cohort of adults with pneumonia.…”
mentioning
confidence: 64%